Cover, Content, and Editorial Note from Borneo J Pharm Vol. 8 No. 1 February 2025 - Borneo J Pharm, Chief Editor of (Borneo Journal of Pharmacy, 2025)
Assalamu’alaikum Wr. Wb. Alhamdulillahirabbil ‘alamin. The next edition of Borneo Journal of Pharmacy (Borneo J Pharm), has been published at February 2025. This edition contains ten articles: Pharmaceutical Regulations, Pharmacology-Toxicology, Clinical-Community Pharmacy, Pharmacognosy-Phytochemistry, Analytical Pharmacy-Medicinal Chemistry, and Natural Product Development, and. This edition includes writings from three countries: Egypt, Indonesia, and Libya. The authors come from several institutions, including Indonesian Food and Drug Authority, Universitas Lambung Mangkurat, Universitas Borneo Lestari, Institut Teknologi Bandung Universitas Muhammadiyah Surabaya, Universitas Mahasaraswati Denpasar, Universitas Muhammadiyah Palangkaraya, Universitas Islam Indonesia, Sekolah Tinggi Ilmu Kesehatan Salsabila Serang, University of Tripoli, Egypt-Japan University of Science and Technology, El Ezaby Pharmacy, Universitas Ahmad Dahlan, IPB University, and Universitas Sriwijaya. Editorial boards are fully aware that there are still room for improvement in this edition, hence with all humility willing to accept constructive suggestions and feedback for improvements to the publication for the next editions. The editorial board would like to thank all editors and reviewers, and contributors of the scientific articles who have provided the repetoire in this issue. We hope that all parties, especially the contributors, could re-participate for the publication in the next edition on May 2025. Wassalamu’alaikum Wr. Wb.